Mini-columns packed with natural zeolites of Cuba for determination of cobalt using the ligand APDC in a flow injection system coupled to a FAAS - Petit de Peña, Yaneira; Rondón, Wendy (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
In this work, an analytical methodology for the determination of traces of cobalt in natural waters by formation of a neutral chelate with ammonium pyrrolidinedithiocarbamate(APDC) was developed. The neutral chelate formed was retained in a column packed with natural zeolites, and then eluted with MIBK to flame atomic absorption spectrometry (EAA) for its detection. The materials were characterized by Fourier Transform infrared spectroscopy and attenuated total reflectance (FTIR and ATR), scanning electron microscopy and energy dispersive X-ray microanalysis (MEB-EDX) and X-ray power diffraction (XRD), indicating that zeolites belong to the family of tectosilicatesClinoptilolite type. Then, use a FIA configuration, with a column preconcentration system coupled to the detection system. The detection limit (3 Âµ) and the relative standard deviation (% RSD), for 10 determinations of a solution of 30 Âµg L”“1 Co2+ and 2.3-4.5%, respectively. The sampling frequency of 27 h-1 and preconcentration factors from 130-160 were achieved, for a sample volume of 6 mL, indicating a high retention of the analyte on the zeolites material.